Unmanned Aerial Vehicles for Real-Time Vegetation Monitoring in Antarctica: A Review - Lockhart, Kaelan; Sandino, Juan; Amarasingam, Narmilan; Hann, Richard; Bollard, Barbara; Gonzalez, Felipe (Remote Sensing, 2025)
The unique challenges of polar ecosystems, coupled with the necessity for high-precision data, make Unmanned Aerial Vehicles (UAVs) an ideal tool for vegetation monitoring and conservation studies in Antarctica. This review draws on existing studies on Antarctic UAV vegetation mapping, focusing on their methodologies, including surveyed locations, flight guidelines, UAV specifications, sensor technologies, data processing techniques, and the use of vegetation indices. Despite the potential of established Machine-Learning (ML) classifiers such as Random Forest, K Nearest Neighbour, and Support Vector Machine, and gradient boosting in the semantic segmentation of UAV-captured images, there is a notable scarcity of research employing Deep Learning (DL) models in these extreme environments. While initial studies suggest that DL models could match or surpass the performance of established classifiers, even on small datasets, the integration of these advanced models into real-time navigation systems on UAVs remains underexplored. This paper evaluates the feasibility of deploying UAVs equipped with adaptive path-planning and real-time semantic segmentation capabilities, which could significantly enhance the efficiency and safety of mapping missions in Antarctica. This review discusses the technological and logistical constraints observed in previous studies and proposes directions for future research to optimise autonomous drone operations in harsh polar conditions.
Keywords: Antarktis; droner; dyp læring; fjernmåling; kartlegging; kunstig intelligens (KI); kybernetikk; maskinlæring; teknologi; vegetasjon

Dronning Maud Land: der ingen skulle tru at det var fjell ... - Engeland, Sveinung; Engeland, Sveinung (Høyde over havet : hvordan fjellene våre ble målt og satt på kartet, 2021)
Keywords: Dronning Maud Land; ekspedisjoner; geografi; kartlegging; oppdagelsesreiser

Sett fra luften - Berg, Thomas Reinertsen (Verdensteater : kartenes historie, 2017)
Keywords: ekspedisjoner; flyfotografering; karthistorie; kartlegging; kartografi

The Mapping of Antarctica - Pedersen, Jakob Søndergård; Curtis, Philip (The Map House, 2012)
Keywords: Antarktis; ekspedisjoner; kart; kartlegging; kartografi; oppdagelsesreiser

Veivisere under sydkorset - Walsøe, Jan Oskar (Sophie Borchgrevink Nordrum og Ivar O. Nordrum, 2012)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; Sydpolen; ekspedisjonen; ekspedisjoner; kartlegging; oppdagelsesreiser; polarområdene

Den Norske Antarktisekspedisjonen 1956-60 : Norway Station (Fimbul) - Henriksen, Hans-Martin (2007)
Keywords: Antarktistraktaten 1959; Den norske antarktisekspedisjonen 1956–1960; Det internasjonale geofysiske år 1957/58; Dronning Maud Land; IGY 1957-58; NAX; geologi; glasiologi; jordmagnetiske målinger; kartlegging; meteorologi; overvintring; tidevannsmålinger

Widerøe kartlegger i Antarktis - Widerøe, Turi (Perspektiv, 2007)
Keywords: Antarktis; Dronning Maud Land; Lars Christensen; Norvegia ekspedisjoner; flyhistorie; hvalfangst; kartlegging

A local geoid in Dronning Maud Land - The NARE 96/97 Geoid - Eiken, Trond; Omang, Ove Christian Dahl; Øvstedal, Ola (IGeS Bulletin, 2001)
The main purpose of the present paper is to estimate the orthometric height of the Global Positioning System (GPS)-station at Troll, Dronning Maud Land, Antarctica. Located at approximately 1300 m above sea level Troll has been connected to the Geodetic Infrastructure forAntarctica (GIANT)-network, but it’s orthometric height remains undetermined. A local geoid has been determined based on gravity-, tidal- and GPS-observations and available gravity anomalies. Information about the ice-thickness has been included in the terrain model. Based on tidal measurements the mean sea level was determined in Jutulgryta, a rift zone in the Fimbulisen ice shelf. Several gravity- and GPS-stations were measured between the two points (Jutulgryta andTroll), a distance of approximately 100 km.
Keywords: Dronning Maud Land; NARE 1996/97; Troll forskningsstasjon; geodesi; kartlegging